Coffee and Potato Agroecosystems: Social Construction of Spaces as a Concept to Analyse Nature's Contributions to People - Bravo-Monroy, Liliana (Frontiers in Ecology and Evolution, 2021)
To achieve goals for conserving and sustainably using nature, decision-making and policy planning require accurate modes of description to understand the interrelationship of society and the environment. Despite most planning strategies are constrained by policy objectives, planning is expected to be more participatory and inclusive of plurality of values and all types of socio-spatial relationships. Based on the Lefebvre’s social theory, the objectives of this work are to: propose a triad of spaces as a helpful framework to analyse Nature’s Contributions to People (NCP); describe different spaces socially constructed by coffee and potato farmer communities in Colombia; and explore implications for various kinds of decision-making. Using qualitative research methods, this manuscript describes three spaces: lived spaces as intangible spaces based on local, religious and ceremonial values of NCP; perceived spaces include farmer spatial organization according to ties of kinship and the downward course of streams; the incidence of negative NCP such as plant diseases, and types of management crops; and conceived spaces as the overlapping of different spatial views of territorial planning. Given that NCP has the great potential of integrating diversity of values about nature and cultural contexts into decision-making, the triad of social spaces offers a spatial dimension to the analyses of NCP. Lived spaces make more visible non-material NCP and non-instrumental values. Perceived spaces highlight material and regulating NCP, the view that maintenance of NCP into the future is essential, and relational and instrumental values e.g., how material and regulating NCP of landscapes are perceived and by whom. Conceived spaces emphasise the predominance of intrinsic biophysical values of NCP. Thus, the triad of social spaces as a conceptual framework can be useful in the operationalization of NCP in environmental management, governance schemes and implementation of land-use plans at the local scale. By thinking spaces relationally, such insights can inform and enhance decisions and policymaking about the value of places toward meeting management priorities. Results emphasise the important policy implications of recognising lived and perceived spaces in decision-making and highlight the role of NCP in facilitating communication of these spaces to support spatial management of land use.